Impact of medication use on quality of life of institutionalized elderly in Northeast Brazil - de Figueiredo Júnior, Lécio; Carvalho Xavier de Medeiros, Caroline Adisson; Vieira Cunha Lima, Sara Iasmin; Antunes de Araujo, Aurigena; Silveira Rebouças Barbosa, Rosa Angélica; Randall Martins, Rand (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2022)
Objective: The evaluation of the quality of life of institutionalized elderly people and the impacts caused by medications. Method: Observational, prospective and transversal study with institutionalized elderly. Data were collected through interviews in ten cities. In addition to socio-demographic data, information on cognition and quality of life was collected. A multivariate logistic regression model was used to identify the drugs and clinical characteristics associated with low quality of life (p <0.05). Results: A predominance of women (60.9%) was observed in the sample of 138 elderly. The mean age was ± 79 years, with a large majority with income equal to or less than a minimum wage (86.2%). Univariate analysis indicated that only angiotensin-converting enzyme inhibitors were factors favoring quality of life. In contrast, the diagnosis of depression, diabetes and higher number of medications worsen quality of life. Among the pharmacological classes also related to the worse quality of life we have the antipsychotics. Conclusion: The quality of life in institutionalized elderly people is negatively affected by a greater quantity of prescription drugs and, above all, by the use of antipsychotics. In contrast, the use of ACE inhibitors has been shown to be related to a better quality of life.